Music Performance Anxiety and Its Relation to Parenting Style and Sensory Processing Sensitivity - Ludivine Aubry; Mats B. Küssner (Jahrbuch Musikpsychologie, 2023)
Music performance anxiety (MPA) is described as a complex phenomenon that arises through an interplay of environmental and personal factors. While previous research has found links between early life experiences and personality traits, the causes and the development of MPA remain poorly understood. This study aimed to assess the role of parenting style and sensory processing sensitivity (SPS) to better understand the causes of MPA. In total, 342 musicians between 18 and 65 years old, active in diverse musical genres in Germany and Austria, were analyzed in the final sample. The abbreviated German version of the Kenny Music Performance Anxiety Inventory (K-MPAI-24) was used to measure MPA. Parenting style was assessed retrospectively using the German version of the Measure of Parenting Style (MOPS) entitled Fragebogen Dysfunktionaler Elterlicher Beziehungsstile (FDEB). To measure the temperamental trait SPS, the German version of the Highly Sensitive Person Scale (HSPS-G) was used. Correlations were calculated to determine the relationships between parenting style and SPS in regard to MPA. Moreover, a moderation analysis was run to examine the interactive effect of parenting style and SPS on MPA. Although no interaction effect was found, the results indicate that abusive and over-controlling parenting as well as enhanced sensitivity may operate as risk factors for experiencing MPA. The present outcomes contribute to a better understanding of MPA and may facilitate supporting performers’ psychological well-being.